Introduction to mathematical modeling using discrete dynamical systems - Marotto, Frederick R. (Thomson Brooks/Cole, 2006)
MATHEMATICAL MODELING USING DISCRETE DYNAMICAL SYSTEMS! This mathematics text introduces powerful mathematical modeling techniques while providing you with the tools you need to succeed. Exercises with answers, suggested computer projects with specific instructions for their completion, and the book-specific website are just a few of the tools that will help you master the material. Coverage of current research, such as dynamical systems, shows you that mathematics is a vibrant and evolving discipline